ANALISIS EFISIENSI PENGGUNAAN SARANA PRODUKSI USAHATANI SEMANGKA (Citrullus vulgaris) DI DESA SUMBER MULYO KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR (JASEP, 2017)
Analysis Of The Efficiency Of The Use Of The Means Of Production Of Farming Watermelon (Citrullus Vulgaris) In The Village Of Source Buay Madang Subdistrict Mulyo District East Of Oku. This research aims to analyze the efficiency of use of production inputs and calculates the magnitude of revenues on a farming Village at the source of the watermelon Mulyo Buay Madang subdistrict of East. The research was carried out in the village of Source Buay Madang Subdistrict Mulyo East, implementation time research was carried out in November until December 2016. Research methods used in this research is a method of field survey on site at the village of watermelon farming Source Mulyo Buay Madang subdistrict of East. Withdrawal methods examples used random stratified method is not balanced. Out of a total population of 275 farmers taken 10% of farmers or 30 farmers. The characteristics of the sample of farmers is the land area of 0, 25 ha up to 0.75 ha i.e. belongs to the category of land. Research results show that for the use of land area gained value NPMx/Px of 6.46 and use of pesticides obtained the value NPMx/Px of the numbers where 25.27 > 1 so that the widespread use of the pesticide has not reached land and efficient. Use of the seed obtained the value NPMx/Px of 0.02, the use of labor earned value NPMx/Px of 0.04 and use of fertilizers obtained the value NPMx/Px of 0.002-where the number 1 so the use of seed <, labor and fertilizers have exceeded efficiently. Revenue Source in the village of watermelon farming Mulyo Buay Madang subdistrict of East obtained amounted to Rp 6,531,500.